Effects of pulse precipitation on soil organic matter mineralization in forests: spatial variation and controlling factors. (11th June 2021) - Jiang, Zhaoxia; Bian, Hongfeng; Xu, Li; Li, Mingxu; He, Nianpeng
Abstract: Aims: Pulse effects of precipitation cause soil organic matter to rapidly decompose and release CO2 in a short period. The pulse effects of precipitation are important for ecosystem C cycling and soil C balance, although their spatial variation in forest soils and the underlying mechanisms remain unclear. Methods: Soil samples (0–10 cm) from 22 typical forest ecosystems in eastern China were used, to investigate the effects of simulated pulse precipitation on soil microbial respiration rates ( R s ). We simulated pulsed precipitation to reach 65% water-holding capacity, the R s was measured on a minute scale for 48 h. Important Findings: Precipitation pulses can cause a rapid 1.70–38.12-fold increase in the rate of mineralized decomposing organic matter. Maximum R s ( R s-soil-max ), cumulative R s ( A Rs-soil ) and the time taken to arrive at the maximal R s ( T Rs-soil-max ) were significant differences among different soil samples. Furthermore, the pulse effects in different climate zones were significantly different. R s-soil-max (11.701 µg C g −1 soil h −1 ) and A Rs-soil (300.712 µg C g −1 soil) were the highest in the mid-temperate zone. Soil chemical properties (total C and, N, pH and oxidation–reduction potential) and soil fractions were strongly correlated with the pulse effects in forest soils, but soil microbes contributed less. Our findings demonstrated that the pulse effects increase forest soil carbon emissions in the short term at a regional scale, and identified the factors with the greatest influence on this change. These findings help guide future studies on the C cycles of forest ecosystems and regulating ecosystem C cycles.